P30 Are we under using diagnostic investigations in the management of abdominal tuberculosis (TB) in high endemic areas of London?. (14th November 2013) - Stevens, C; Sithamparanathan, S; O'Shaughnessy, T
Abstract : Introduction: Abdominal tuberculosis presents with non-specific clinical symptoms. Diagnosis is based on clinical reasoning supported by radiological findings either by ultrasound or computer tomography. The gold standard of diagnosis remains with culture Mycobacteria tuberculosis complex. Therefore in areas with high endemic rates of TB are we under using investigations to gain tissues samples in suspected cases? Method: We undertook a retrospective analysis of 46 cases coded as abdominal tuberculosis from our local hospital register. Data was collected from case notes and computer systems regarding pathology and radiology results. Results: The majority of patients were born in the Indian subcontinent: India 39%, Pakistan 20% and Bangladesh 8%. More than half the patients had lived in the UK for less than 5 years. 54% of patients had symptoms for 1–4 months before presentation. None of the cases had TB in the past and 13% could recall possible TB contact. 67% of CXR was normal, and of those who had abnormal films, only 4 cases had features that were specific for TB. Focused imaging taken included: CT abdomen 77%, US abdomen 18%, MR abdomen 1%, Barium follow through 5%. 48% of patients had procedures to obtain histological and microbiological results, including laparoscopy, laparotomy, colonoscopy, gastroscopy or ascitic tap. 26% of patients underwent laparoscopy. Of the remaining patients, 18% obtained microbiological samples from alternative sites. Thus, 42% patients were treated on clinical symptoms and radiological image findings alone. Discussion: Laparoscopy has been regarded as the gold standard and diagnostic investigation of choice in the management of abdominal TB 1, 2 . In our cohort 26% underwent laparoscopy. The reason for this unclear but could be due perceived risk with the procedure, lack of availability of service or in many cases is used as a last resort. In TB endemic areas, we suggest the development of an acceptable evidence based investigational pathway incorporating our surgical and gastrointestinal colleagues leading to more prompt and through management of abdominal tuberculosis. References: McLaughlin S, Jones T, Pitcher M, Evans P. Laparoscopic diagnosis of abdominal tuberculosis. Aust NZ J Surg 1998;68: 599–601 Rai S, Thomas W M. Diagnosis of abdominal tuberculosis: the importance of laparoscopy. J R Soc Med . 2003 December; 96(12): 586–588.